Invitro dissolution studies of lansoprazole EC pellets 12% w/w – A comparative dissolution profile with reference sample - VENKATESWARA REDDY BOYA; DR. K. S. SEKHARA RAO (International Journal of Pharma and Bio Sciences, 2018)
The purpose of this study was carried out to prove better invitro results of Lansoprazole EC Pellets 12% w/w in comparison with market reference sample (Cipla Pharmaceuticals Ltd.). This study was conducted on antiulcer drug for the treatment of ulcers, as many people are getting affected from ulcers worldwide. One of the popular drug Lansoprazole is a Proton Pump Inhibitor (PPI) which helps to reduce acid secretion from parietal cells. Lansoprazole and LANZOL-30 samples were tested for comparative dissolution studies in multimedia of 0.1N Hydrochloric acid, pH 4.5 Acetate buffer, pH 6.8 Phosphate buffer for 12 units each by using method reference from USP-41. The Comparative Dissolution Profile (CDP) of Lansoprazole EC Pellets 12% w/w sample was found good when compared with reference sample of LANZOL-30. The f2 values were found more than 50 (89 in 0.1 N HCl, 75 in pH 4.5 Acetate buffer & 73 in pH 6.8 Phosphate buffer) in all the three media with reference to dissolution guidelines of Medicines Control Council (MCC), South Africa. Thus, the CDP was considered acceptable and better invitro results have been achieved for the formulation Lansoprazole EC Pellets 12% w/w.